Mobile Phone Programming Application to Wireless Networking - Fitzek, Frank H. P.; Reichert, Frank; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book provides a solid overview of mobile phone programming targeting both academia and industry. Mobile Phone Programming covers all commercial realizations of Symbian, Windows Mobile and Linux platforms. Each programming language (JAVA, Python, C/C++) and a set of development environments are introduced "step by step" making developers familiar with current limitations, pitfalls, and challenges. Each chapter contains examples and source code to rapidly make developers familiar with the most important concepts. Examples cover peer to peer networks, cooperative networking, cross layer protocol design, key challenges such as power consumption, and sensor networks for which a full hardware and software implementation is provided. Whether you are an experienced developer or an advanced student Mobile Phone Programming will be your key reference for successfully entering the world of software development for mobile devices.
to Mobile Phone Programming -- Mobile Phone Programming Languages -- Python for Symbian Phones -- Java 2 Micro Edition -- Symbian/C++ -- Open C -- Qtopia Greenphone -- Maemo Linux -- Windows Mobile Programming -- Infrastructure-Based Communication -- Service Discovery -- Peer-to-Peer Communication -- Digital Ownership for P2P Networks -- SMARTEX: The SmartME Application -- The Walkie Talkie Application -- Cooperative Communication -- Cooperative Wireless Networking: An Introductory Overview -- The Medium is the Message -- Peer-to-Peer File Sharing for Mobile Devices -- Energy Saving Aspects and Services for Cooperative Wireless Networks -- Cross-Layer Communication -- Cross-Layer Protocol Design for Wireless Communication -- Cross-Layer Example for Multimedia Services over Bluetooth -- Sensor Networks -- Convergence of Mobile Devices and Wireless Sensor Networks -- Using In-built RFID/NFC, Cameras, and 3D Accelerometers as Mobile Phone Sensors -- Sensor Networks for Distributed Computing -- Parking Assistant Application -- Power Consumption in Mobile Devices -- Energy Efficiency of Video Decoder Implementations -- External Energy Consumption Measurements on Mobile Phones -- Optimizing Mobile Software with Built-in Power Profiling.
Keywords: ENGINEERING; COMPUTER SCIENCE; MICROWAVES; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; SIGNAL, IMAGE AND SPEECH PROCESSING; MICROWAVES, RF AND OPTICAL ENGINEERING; PROGRAMMING TECHNIQUES